New provisional serovar (E10163) of Shigella boydii. - Gross, R J (1980)
Eleven bacterial strains are described which give the biochemical reactions characteristic of the genus Shigella but do not belong to any of the established or provisional serovars. The strains are biochemically and serologically indistinguishable, and it is proposed that they be regarded as members of a new provisional serovar of Shigella boydii. Strain E10163 is designated as the test strain for this new serovar.